Retrospective view and treatment of iatrogenic ureteral injuries (Annals of Medical Research, 2021)
Aim: Ureteral injuries are rare. Iatrogenic ureteral injury is the most common cause of ureteral traumas. This letter aims, evaluation of iatrogenic ureteral traumas and treatments.Material and Methods: Thirty two patients with major iatrogenic ureteral trauma were enrolled. Sonography, intravenous pyelography, CT of abdomen (contrast-enhanced and non-contrast enhanced), antegrade X-rays or diagnostic ureterenoscopy are used for the diagnosis. All patients were undergone endoscopic ureterenoscopy before the ureter was surgically repaired. Next, the surgical technique was decided. Injuries that can be managed with endoscopic approach were treated by inserting a Double J stent. For patients who were not eligible for endoscopic treatment, treatment was decided according to the location of ureteral injury.Results: Of the patients, 25 were female and 7 were male and mean age was 46.31±16.485 years. Ureteral injury was secondary to gynecologic intervention in 16 patients, general surgery procedures in 6 patients and urologic surgery in 10 patients. According to AAST, Grade 4-5 injury was identified in 71.9% of 32 patients, while Grade 3 and Grade 2 injuries were noted in 15.6% and 12.5% of patients, respectively. Four patients were treated in late period, while intraoperative or early treatment was instituted for 28 patients.Conclusion: Iatrogenic ureteral injuries develop mostly after laparoscopic or endoscopic pelvic surgeries. We should prefer endoscopic insertion of Double J stent for the first-line treatment.
Keywords: Latrogenic; ureter; traumas; treatment